The burden of coronary heart disease in simultaneous pancreas-kidney transplantation - Marques, Joana (2022)
INTRODUCTION: Type 1 diabetes mellitus is associated with an increased risk of coronary artery disease, which is frequently asymptomatic. This risk increases significantly in those with nephropathy. In selected patients, simultaneous pancreas-kidney transplantation is the renal and pancreatic replacement therapy of choice, as it increases longevity and stabilizes diabetic complications. Despite essential, universal screening protocols are still controversial for coronary artery disease in this population. METHODS: We retrospectively analysed 99 simultaneous pancreas-kidney recipients from our centre from 2011 to 2018 and selected 77 patients who underwent coronary angiography during the pre-transplant evaluation. Our aim was to identify potential risk factors associated with significant lesions on coronary angiography. RESULTS: Almost half of our cohort of 77 candidates submitted to coronary angiography had coronary artery disease. Of these, nearly 30% underwent revascularization, although only one of them reported symptoms of myocardial ischemia. In a univariate analysis, the presence of smoking habits was the only risk factor for coronary artery disease. We also found that 20 or more years of type 1 diabetes mellitus was significantly associated with the presence of coronaropathy. DISCUSSION: Selection of diabetic candidates with acceptable cardiac risk before simultaneous pancreas-kidney transplantation is imperative. Given the impact of a correct diagnosis and a low procedural risk, we defend the routine use of coronary angiography as the initial screening method for coronary artery disease in this population. Particularly care must be taken in evaluating asymptomatic patients with long-term type 1 diabetes mellitus and smokers.